Liposomes and liposome-like nanoparticles: From anti-fungal infection to the COVID-19 pandemic treatment - Yonglong He; Wanting Zhang; Qingqing Xiao; Lifang Fan; Dechun Huang; Wei Chen; Wei He (Elsevier, 2022)
The liposome is the first nanomedicine transformed into the market and applied to human patients. Since then, such phospholipid bilayer vesicles have undergone technological advancements in delivering small molecular-weight compounds and biological drugs. Numerous investigations about liposome uses were conducted in different treatment fields, including anti-tumor, anti-fungal, anti-bacterial, and clinical analgesia, owing to liposome's ability to reduce drug cytotoxicity and improve the therapeutic efficacy and combinatorial delivery. In particular, two liposomal vaccines were approved in 2021 to combat COVID-19. Herein, the clinically used liposomes are reviewed by introducing various liposomal preparations in detail that are currently proceeding in the clinic or on the market. Finally, we discuss the challenges of developing liposomes and cutting-edge liposomal delivery for biological drugs and combination therapy.